2015
DOI: 10.5796/electrochemistry.83.406
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Corrosion Performance of Low Alloy Steel in Acid Sodium Chloride Solution

Abstract: The corrosion behavior of low alloy steel for cargo oil tanks (COT) is investigated by thermo mechanical control process (TMCP) at various cooling rates. The corrosion rate is estimated by accelerated corrosion test in strong acid sodium chloride solution. The corrosion mechanism is studied by potentiodynamic polarization curve and electrochemical impedance spectroscopy (EIS) measurements. It indicates that the acicular ferrite is refined as the cooling rate increases, the CR15 steel with higher cooling rate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…These plots show that the current density increased as the applied potential increased. This agreed with literature reports [7,22,23]which suggest that current density increased with potential within the active region due to activation control reaction. It is also evident from Fig.…”
Section: Potentiostatic Polarization Measurementssupporting
confidence: 93%
See 2 more Smart Citations
“…These plots show that the current density increased as the applied potential increased. This agreed with literature reports [7,22,23]which suggest that current density increased with potential within the active region due to activation control reaction. It is also evident from Fig.…”
Section: Potentiostatic Polarization Measurementssupporting
confidence: 93%
“…This effect was attributed to micro-galvanic effect. The EIS results are in agreement with the trend of the corrosion film formed at different potentials demonstrating a decline in impedance as the applied potential is increased [15,23]. To further buttress the reliability and effectiveness of the fitted data for the proposed EC, the relative residual errors for the real ( re) and imaginary ( im) components of the impendence were calculated using Eqs.…”
Section: Figsupporting
confidence: 65%
See 1 more Smart Citation
“…It can be observed from Figure 2 that the plots of potential (vs OCP) versus current density are similar for all the steel specimens in both pH and temperature conditions suggesting that the corrosion mechanism is the same 31,32 . The anodic current densities increased with increase in potential particularly within the low overvoltage depicting a welldefined Tafel slopes.…”
Section: Tafel Polarizationmentioning
confidence: 79%
“…From this figure, it can be observed that all the specimens exhibited the same corrosion behaviour of a continuous increase in anodic current with increase in corrosion potentials thus displaying a well-defined Tafel region in both solutions. This suggests that passive film was not formed [20][21][22]. On the other hand, the cathodic polarization curves for all the steels showed a mixed activation-and diffusion-controlled characteristics for all the steels.…”
Section: Figure 1: Lpr Corrosion Rate Of the Steels In (A) Co2 Saturamentioning
confidence: 87%